"By Taste and the Spirit of the Times …": The Professor as Slave. Issue 10 (2nd December 2017) - Kabatskov, A.N.; Leybovich, O.L.
Abstract : The authors examine how the social status of the university professor has evolved in Russia in recent centuries in light of the historical concepts about the enslavement and emancipation of social groups proposed by Sergey Solovyov and Aleksandr Gradovsky. They use the metaphor of the "slave" [nevol'nik] to describe the dependent position of the professor in the university. The word encapsulates administrative tyranny, the spread of subordinate and submissive mentality in the university environment, and the curtailment of opportunities for professional self-fulfillment. The authors present the university administration as the main agent responsible for enslaving professors. Administrators represent bureaucratic power and act to advance their own social ambitions.